Beyond the Stigma: Leveraging Education and Empathy for Effective Tuberculosis Care - Wahyuningsih, Aries; Probandari, Ari; Sumardiyono; I Wayan Gede Artawan Putra; Firmanda, Giovanni Iga (Babali Publisher, 2025)
Introduction: Tuberculosis (TB) remains a major global health issue, with stigma continuing to hinder effective prevention, diagnosis, and treatment. Stigma can discourage patients from seeking care, adhering to treatment, and engaging with healthcare providers. This systematic review aims to identify stigma-related issues in TB and explore practical strategies to reduce stigma.Methods: A scoping literature search was conducted for studies published between 2012 and 2024 using ProQuest, PubMed, and ScienceDirect databases. Articles were selected based on predefined inclusion and exclusion criteria, and the review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The Joanna Briggs Institute (JBI) methodology was used for critical appraisal and synthesis.Results: A total of 15 articles were included in the final analysis. The findings indicate that key strategies to reduce TB stigma include health education to correct misconceptions, promoting empathy, and non-discriminatory attitudes among healthcare providers. Educational interventions raise awareness and dispel myths, while empathetic care fosters trust and reduces negative perceptions. Cultural understanding enhances communication and patient engagement. Despite these efforts, TB-related stigma remains pervasive and continues to be a barrier to effective care.Conclusion: The review concludes that current interventions are insufficient and that sustained, targeted strategies focusing on education, empathy, and cultural competence are essential to reduce stigma and improve TB outcomes. A long-term commitment to these approaches is critical to advancing TB control efforts globally.